The forever summer : a novel - Brenner, Jamie, 1971- (Little, Brown and Company, 2017)
Marin Bishop has always played by the rules, and it's paid off: on the cusp of thirty she has a handsome fiancé, a prestigious Manhattan legal career, and her father's hard-won admiration. But with one careless mistake at work, Marin suddenly finds herself unemployed and alone. Before she can summon the courage to tell her parents, a young woman appears, claiming to be Marin's half-sister. Seeking answers, Marin agrees to join her on a soul-searching journey to Cape Cod, to meet the family she didn't even know she had. As the summer unfolds at her grandmother's beachside B&B, it becomes clear that her half-sister's existence is just the first in a series of truths that will shake Marin's beliefs--in love, and in her own identity--to the core. Filled with shocking revelations, heartfelt romance, and resilient women banding together against the most unexpected twists of fate, THE FOREVER SUMMER is an emotionally resonant page-turner, and a delicious escape for any season.